Long-term follow-up after stent graft placement for access-site and access-related vascular injury during TAVI – The Bonn-Copenhagen experience. (15th April 2019) - Sedaghat, Alexander; Hansen, Kristoffer Lindskov; Schahab, Nadjib; May, Maria Cesarina; Weber, Marcel; Stundl, Anja; Shamekhi, Jasmin; Schaefer, Christian; Nickenig, Georg; Sinning, Jan-Malte; Lönn, Lars; Søndergaard, Lars; et al.
Abstract: Aims: Stent graft placement is a safe and effective treatment option for vascular complications in the context of transcatheter aortic valve implantation (TAVI). This study aimed to provide long-term angiological follow-up of stent grafts used for this indication. Methods and results: Seventy-one patients (64.8% female, log EuroScore 14.7 ± 6.8%) who had undergone TAVI between March 2010 and October 2015 with implantation of a Viabahn or Fluency stent graft to treat access-site or access-related vascular injury (ASARVI) were analyzed. Implantations were mostly due to access-site bleeding complications (83.1%) in the common femoral artery (97.1%). Follow-up was performed with duplex sonography in all patients after a median of 3.9 years after TAVI (interquartile range [IQR]: 895–1749 days). Ultrasound revealed tri- or biphasic flow patterns in 16.9% and 77.6%, respectively. Stent graft patency was 100% without signs of stent graft stenosis (mean peak velocity ratio 1.0 ± 0.2). Pseudo-aneurysms or endoleaks were diagnosed in 5.6% of patients. Additional fluoroscopic and/or computed tomography (CT)-imaging was available in 36.6% of patients and did not reveal any stent fracture. Conclusion: Self-expanding stent grafts provide excellent long-term function with few complications when implanted in the context of TAVI-related ASARVI. Highlights: Long-term data on stent grafts used in TAVI-related vascular complications is missing. In this study we analyzed seventy-one patients treated with two different stent grafts. After a median of 3.9 years, no stent stenosis or stent fracture was observed. Pseudo-aneurysms or endoleaks were observed in 5.6% of patients. Stent grafts provide a durable treatment for TAVI-related vascular complications.